Reduction of Microvessel Number and Length in the Cerebellum of Purkinje Cell Degeneration Mice - Kolinko, Yaroslav; Kralickova, Milena; Cendelin, Jan (Cerebellum, 2024)
Degenerative effects of nerve tissues are often accompanied by changes in vascularization. In this regard, knowledge about hereditary cerebellar degeneration is limited. In this study, we compared the vascularity of the individual cerebellar components of 3-month-old wild-type mice (n = 8) and Purkinje cell degeneration (pcd) mutant mice, which represent a model of hereditary cerebellar degeneration (n = 8). Systematic random samples of tissue sections were processed, and laminin was immunostained to visualize microvessels. A computer-assisted stereology system was used to quantify microvessel parameters including total number, total length, and associated densities in cerebellar layers. Our results in pcd mice revealed a 45% (p < 0.01) reduction in the total volume of the cerebellum, a 28% (p < 0.05) reduction in the total number of vessels and a lower total length, approaching 50% (p < 0.001), compared to the control mice. In pcd mutants, cerebellar degeneration is accompanied by significant reduction in the microvascular network that is proportional to the cerebellar volume reduction therefore does not change density of in the cerebellar gray matter of pcd mice.
Keywords: Animals; mikrocévy; Mice, Neurologic Mutants; Mice, Inbred C57BL; Purkinje Cells; mozeček; Purkyňovy buňky; Cerebellum; myši; Microvessels; zvířata; myši - mutanty neurologické; myši inbrední C57BL; Mice